HUBUNGAN KEPEMIMPINAN KEPALA MADRASAH DENGAN CITRA LEMBAGA - Aep Tata Suryana; Zenda Kirana (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
A leader in educational institutions is often the attention of experts, in this case, especially with regard to the leadership of the head of the madrasa as the main person in charge of the existence of an educational institution, the problem in this study is how the leadership of the head of the madrasa in improving the good image of the institution in the eyes of the community. This study aims to determine the relationship between Madrasah Principal Leadership and Institutional Image at State Madrasahs in Sumedang Regency. This research method uses a quantitative approach with the type of correlational method. Based on the results of the study, it showed that the leadership of the Head of State Madrasahs in Sumedang Regency included very high qualifications, namely 4.26 in the interval range of 4.20 – 5.00. The image of the institution is included in the very high qualification of 4.29 which is found in the interval range of 4.20 - 5.00. The results obtained from the correlation of the significance of the relationship between the leadership of the madrasah principal and the image of the institution obtained 0.000. Therefore, the value of 0.000 <0.005 and the value of the correlation coefficient of 0.528 is in the interval value of 0.51 - 0.75, which means that the leadership of the madrasa head has a very strong relationship with the image of the institution. Then the coefficient of determination R Square 0.278 means that the contribution of the leadership variable of the madrasa principal to the image of the institution is 27.8%